Laparoscopy in patients with chronic pelvic pain in the North Central Hospital - IPSS Chiclayo. - Herrera Vega, Carlos (2015)
IPSS Chiclayo - 90 laparoscopy between October 31, 1987 to October 31, 1988 in the North Central Hospital were performed. The indications for laparoscopy was our Chronic Pelvic Pain in patients who were admitted to outpatient derived Unit laparoscopic gynecology service; of which 53.3% (48 cases), pelvic pain and showed only 46.7% (42 cases), pelvic pain associated with other symptoms.